The Three Teachings of East Asia (TTEA) Inventory: Developing and Validating a Measure of the Interrelated Ideologies of Confucianism, Buddhism, and Taoism - Lin, Yi-Ying; Swanson, Dena Phillips; Rogge, Ronald David (Frontiers in Psychology, 2021)
Objectives: Buddhism, Taoism, and Confucianism have influenced societies and shaped cultures as they have spread across the span of history and ultimately across the world. However, to date, the interrelated nature of their impacts has yet to be examined largely due to the lack of a measure that comprehensively assesses their various tenets. Building on a conceptual integration of foundational texts on each ideology as well as on recent measure development work (much of which is unpublished), the current studies developed a comprehensive measure of these ideologies (the Three Teachings of East Asia Inventory; TTEA) and validated it across 4 languages. Methods: A combined sample of 2,091 online respondents (Study1: 322 Chinese respondents, Study2: 400 Japanese respondents, Study3: 362 Taiwanese respondents, Study4: 688 White Americans and 319 Asian Americans) completed 25-35 min online survey in their preferred language: English, Traditional Mandarin, Simplified Mandarin, or Japanese. Results: Exploratory Factor Analyses within a 122-item pool identified 18 stable dimensions across all samples. Measurement invariance analyses identified the final 61-items of the TTEA inventory (demonstrating reasonable invariance across all languages), confirming 18 individual tenet subscales that organize into 4 higher-order composites: Buddhism, Taoism, Restrictive Confucianism, and Empowering Confucianism. A shorter 36-item version of the TTEA inventory was also developed. The TTEA scales demonstrated (1) acceptable internal consistency, (2) discriminant validity, and (3) incremental predictive validity for current life satisfaction and vitality. Conclusions: The TTEA inventory offers one of the first comprehensive, multilingual measures that will allow cross-cultural researchers to examine the influence of three related Eastern ideologies on societies across the world.